Ischemic stroke due to protein C deficiency - Saha, Debasish Kumar; Ahsan, ASM Areef; Fatema, Kaniz; Saha, Madhurima; Ahmed, Fatema; Asrafuzzaman, Md; Morshed, MM; Raz, Farhana; Hassan, Md Rashidul; Ahmed, Abdullah Al; et al. (Bangladesh Critical Care Journal, 2016)
Cardiovascular diseases are one of the common causes of high morbidity and mortality all over the world. Usually stroke occur in elderly, but stroke in younger group (age <45 years) are increasingly common now-a-days. The disease can occur in young patients without any apparent risk factors. It is therefore important to exclude all aetiological causes in order to reduce their chances for a subsequent event. Bangladesh Crit Care J September 2016; 4 (2): 123-124